THE LEADERSHIP AND MANAGEMENT SKILLS FOR SERVICE DELIVERY IN SOUTH AFRICAN MUNICIPALITIES: A COMPROMISED REQUIREMENT? - Sebola, Mokoko (Journal of Social Political Sciences, 2024)
Municipal service delivery remains a persistent issue in South African municipalities, which has been a subject of both academic inquiry and political debate. Despite extensive attention, the roles of leadership and management as key variables influencing service delivery have not been thoroughly explored. This study investigates the impact of leadership and management on municipal service delivery inefficiencies. Using a conceptual approach, data were collected through a desktop study to examine the extent to which political leadership in South Africa overlooks the significance of leadership and management skills in service delivery. The findings suggest that the neglect of these skills within municipal administration contributes significantly to service delivery failures. The paper concludes that incorporating leadership and management competencies into the governance of South African municipalities is essential for improving service delivery outcomes.